Arabic Film and the Construction of Nationalism: A Study of Palestinian Cinema in the Film The Present (2021) - Musa, Muhammad Ali (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the construction of Palestinian nationalism in the film The Present (2021) by Farah Nabulsi. As a work of modern Arab cinema, this short film presents an alternative depiction of resistance, not by highlighting acts of physical violence, but by portraying the daily struggles of Palestinians under Israeli military occupation. Through a descriptive qualitative research method, employing approaches of perception, analysis, and representation, this study examines how the values of nationalism are reflected in the experiences of the main characters, Yusef and his daughter Yasmine, as they navigate a military checkpoint. The primary data source is the film The Present, while supplementary data were obtained from literature reviews, prioritizing accredited Indonesian scholarly journal articles, such as those from Arabi: Journal of Arabic Studies, which discuss Palestinian cinema and nationalism. To complement the analysis, this study also refers to publications from international research institutions, online media reports, and expert perspectives relevant to the Palestinian issue and media representation. The findings indicate that nationalism in this film is constructed through three main pillars. First, the definition of the "existence of the other," in which Israeli soldiers are depicted as bureaucratic and dehumanized instruments of occupation, thereby reinforcing Palestinian identity as an oppressed, colonized nation that nevertheless perseveres. Second, everyday resistance (sumud), reflected in Yusef’s steadfastness in enduring absurd daily routines for the sake of his family, is a form of passive resistance that effectively undermines the moral legitimacy of the occupier. Third, the intergenerational transfer of nationalism, portrayed through Yasmine’s character; Yasmine’s actions at the end of the film demonstrate how nationalistic values are passed from parent to child, also serving as the seeds of future resistance. The film affirms that Palestinian nationalism does not always equate to armed resistance, but also involves endurance, preserving dignity (karamah), and manifesting a narrative of humanity amidst oppressive occupation. The success of The Present in winning an Oscar also strengthens the position of cinema as an effective tool of cultural diplomacy for the Palestinian people.